Parole e cose Raccolta di scritti minori - Boscherini, Silvano (Biblioteca di Studi di Filologia Moderna, 2016)
Parole e cose ("Words and Things") collects the works by Silvano Boscherini (1920-2010), Full Professor of Latin Literature in Florence, published on magazine during his long academic activity. The volume is a proof of Boscherini's scientific interests and, in addition to being a tribute to the man and the scholar, proposes still valid contributions in terms of knowledge and, above all, in terms of method. The works are divided into the five fundamental areas analysed by Boscherini over the years, even if a single article cannot always be uniquely placed in a single section, precisely because of the global and historicist method with which Boscherini has always faced the study and the examination of the texts. Within each section the works are proposed in chronological order.